1987
DOI: 10.3406/paleo.1987.4426
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Slab Construction; A Conservative Southwest Asiatic Ceramic Tradition, ca. 7000-3000 B.C.

Abstract: Afin de saisir les techniques de fabrication et de production de la poterie utilisées entre 7000 et 3000 avant J.-C, dans le Zagros, région montagneuse du Sud-Ouest asiatique, et afin de spécifier les modes de changement technologique, il fut procédé à l'examen macroscopique de 40 000 fragments et à l'analvse des microstructures de 4 000 tessons. Pour mieux évaluer tant la rapidité des changements technologiques observés que le rôle de certains facteurs contraignants (propriété des argiles, disponibilité des m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
4

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 2 publications
1
34
0
4
Order By: Relevance
“…Many scholars have employed radiography successfully (e.g. Carmichael, 1990Carmichael, , 1998Ellingson et al, 1988;Foster, 1983;Henrickson, 1991;Levi, 1999;Nenk and Walker, 1991;Philpotts and Wilson, 1994;van Beek, 1969;Vandiver et al, 1991;Vandiver and Tumosa, 1995), but the two most detailed case studies were undertaken by scholars working in the Near East (Glanzman, 1983;Glanzman and Fleming, 1986;Vandiver, 1987. Some of the more intriguing case studies have utilised X-radiography to detect hidden vessel parts and added sections, such as the whistling mechanism in Peruvian pots and the fake spout of Aegean stirrup jars (Digby, 1948;Leonard et al, 1993).…”
Section: Identifying Vessel Formation Proceduresmentioning
confidence: 98%
“…Many scholars have employed radiography successfully (e.g. Carmichael, 1990Carmichael, , 1998Ellingson et al, 1988;Foster, 1983;Henrickson, 1991;Levi, 1999;Nenk and Walker, 1991;Philpotts and Wilson, 1994;van Beek, 1969;Vandiver et al, 1991;Vandiver and Tumosa, 1995), but the two most detailed case studies were undertaken by scholars working in the Near East (Glanzman, 1983;Glanzman and Fleming, 1986;Vandiver, 1987. Some of the more intriguing case studies have utilised X-radiography to detect hidden vessel parts and added sections, such as the whistling mechanism in Peruvian pots and the fake spout of Aegean stirrup jars (Digby, 1948;Leonard et al, 1993).…”
Section: Identifying Vessel Formation Proceduresmentioning
confidence: 98%
“…medical checkups, non-destructive material analysis, mineral or metallurgical content analysis, X-ray imaging techniques have been demonstrated to provide valuable qualitative data on the internal structure of most of the living creatures and materials. The use of X-ray imaging to assess variability in ceramic fabrication is common in archaeological studies aimed at examining ancient pottery technologies [1][2][3][4][5][6][7]. These studies are based on empirical observations that the various deformation rates applied to clay for forming vessels according to different techniques, induce specific structural patterns that may be detected visually on X-radiographs.…”
Section: Introductionmentioning
confidence: 99%
“…see Rye, 1977Rye, , 1981Vandiver, 1987;McGovern, 1989;Carr, 1990;Vandiver et al, 1991;Blackmann, Stein & Vandiver, 1993). Key indicators visible on radiographs consist mainly of orientation of particles and voids and shapes of voids (Vandiver, 1987;Carr, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Rye (1981: 60) reported that a skilled potter can infer much of the forming process by feeling subtle variations in thickness and reconstructing the finger and hand movements of the maker. Gradual thinning of the wall thickness from the base to the rims and/or an extreme regularity of wall thickness in horizontal sections have been used to characterize thrown vessels (Picon, 1973;Rye, 1981;Balfet, Fauvet-Berthelot & Monzon, 1983;Vandiver, 1987;Mery, 1991). Given these numerous observations, surprisingly little is known about the significance of this macrofeature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation